Management of Junior High School Science Laboratory for Students’ Practical Activities: Pengelolaan Laboratorium Sains Sekolah Menengah Pertama untuk Kegiatan Praktik Siswa - Ira Puspita; Ria Wulandari (Academia Open, 2026)
General Background: Science laboratories are essential educational facilities supporting practical activities that connect scientific concepts with hands-on experiences in junior high schools. Specific Background: Effective laboratory management is required to ensure systematic planning, organization, implementation, and evaluation of science practicum activities within school contexts. Knowledge Gap: Despite the availability of laboratory facilities, detailed descriptions of how laboratory management is practically implemented at the junior high school level remain limited, particularly regarding administrative consistency, safety facilities, and evaluation mechanisms. Aims: This study aims to describe the management of a science laboratory in a private junior high school in Sidoarjo as it relates to students’ practical activities. Results: Using a qualitative case study approach, findings indicate that laboratory management has been implemented consistently in planning, organizing, and conducting practicum activities, involving curriculum units, laboratory managers, and science teachers. Practicum schedules were stable, organizational structures were formally established, and practicum implementation followed planned procedures with documented inventories and student reports. However, weaknesses were identified in documentation completeness, flexibility of planning revisions, systematic tool borrowing records, adequacy of safety equipment, and laboratory-specific evaluation forums. Novelty: This study provides an in-depth empirical description of integrated laboratory management practices and their operational challenges within a private junior high school context. Implications: The findings highlight the need for improved administrative documentation, strengthened safety management, and more focused evaluation mechanisms to support sustainable science laboratory operations and practice-based science learning. HighlightS: Laboratory planning and practicum scheduling were conducted collaboratively and applied consistently throughout the academic year. Organizational structures and practicum implementation procedures were formally established but lacked comprehensive administrative records. Evaluation and monitoring were responsive at the school level, yet laboratory-focused reporting and safety provisions remained limited. Keywords: Laboratory Management, Science Practicum, Students, Learning